Energy and exergy aanalyses of drying of eggplant slices in a cyclone type dryer - Akpinar, EK (Korean Soc Mechanical Engineers, 2005)
In this paper, the energy and exergy analyses of the drying process of thin layer of eggplant slices are investigated. Drying experiments were conducted at inlet temperatures of drying air of 55, 65 and 75 degrees C and at drying air velocities of 1 and 1.5 ms(-1) in a cyclone type dryer. Using the First law of thermodynamics, energy analysis was carried to estimate the ratios of energy utilization. However, exergy analysis was accomplished to determine type and magnitude of exergy losses during the drying process by applying the second law of thermodynamics. It was deduced that eggplant slices are sufficiently dried in the ranges between 55-75 degrees C of drying air temperature and at I and 1.5 ms-1 of drying air velocity during 12000-21600 s despite the exergy losses of 0-0.739 kJs(-1).
Keywords: drying; energy and exergy analyses; eggplant